Notes on Early Land Plants Today. 20. New synonyms in Gymnocoleopsis (Cephaloziellaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Gymnocoleopsis multiflora was shown, based on molecular analysis by de Roo et al. (2007) not to belong to Lophoziaceae, but rather to Cephaloziellaceae and was transferred there by Crandall-Stotler et al. (2009). This transfer is also supported by some morphological characteristics like the cross section of the seta which is similar to that of other species of Cephaloziellaceae.